Linking Sharia Bank Corporate Image and Customer Trust with Customer Switching Intention: The Mediating Role of Customer Loyalty - Mariska SR HS; Miftakhul Khasanah; Sutrisno (Journal of Islamic Economic and Business Research, 2022)
Good service from a bank will be an added value to improve the company's image and is directly proportional to customer loyalty. Customer loyalty can prevent customers from switching to using services from other companies. This study aims to examine the role of the mediating variable, customer loyalty, which relates to the effect of company image and trust on customer intention to switch. The object of this research is the customer of Bank Muamalat Indonesia. After reviewing the literature and formulating hypotheses, the data collected through the questionnaire method were 213 respondents from Bank Muamalat Indonesia customers. The sampling applied the convenience sampling technique. The data obtained were then analyzed using Structural Equation Modeling (SEM), while the hypothesis test used the Smart-PLS 3.0 application. This study indicates that loyalty can fully mediate the influence of company image and trust on switching intention. Creating loyalty means building customer image and trust as a company investment in the long term. Managers need to build corporate image and customer trust to compete in Indonesia's financial industry.